Hubungan Status Nutrisi terhadap Hiperemesis Gravidarum pada Ibu Hamil di Puskesmas Tanah Jambo Aye Aceh Utara Tahun 2024 - Miyanti Febrina; Ester Simanullang (Pusat Riset dan Inovasi Nasional, 2025)
Hyperemesis gravidarum is excessive nausea and vomiting in pregnant women which interferes with daily activities because it is usually made worse by dehydration. The cause of hyperemesis gravidarum is not known for certain, but it is likely caused by an increase in the serum hormones estrogen and HCG (chorionic gonadotropin hormone). The aim of this research is to analyze the relationship between nutritional status and hyperemesis gravidarum in pregnant women at Tanah Jambo Aye Community Health Center, North Aceh. This study used a case control design. Pain Case Study This research was conducted to determine whether parity, nutritional status and stress are related to hyperemesis gravidarum in pregnant women. There is a relationship between nutritional status and the incidence of hyperemesis gravidarum in pregnant women at the Tanah Jambo Aye Community Health Center, North Aceh. Pregnant women with poor nutritional status will experience hyperemesis gravidarum 7.5 times compared to pregnant women with good nutritional status. Pregnant women are expected to always seek information about hyperemesis gravidarum and risk factors for hyperemesis gravidarum.